Operational risk management framework - BPN Paribas - Souza, Opal Nassim Mabel de (2021)
The scope of this empirical study was developed within the NOVA SBE Work Project Direct Internship Programme, involving the analysis of selected processes entailed by the ORM framework at BNP Paribas. Operational Risk will constantly threaten to subvert financial institutions, hence regulators require banks to have effective Operational Risk Management (ORM) systems, so that potentially significant risks are detected and mitigated at the earliest, to safeguard stakeholders’ interests (McKinsey 2016). This work project researches the relevance of the ORM model of BNP Paribas Global Markets department by examining the processes and their associated risks. By studying the operational risk trends from past incidents to identify, evaluate, and measure operational risks existence, a risk map is determined and an internal control system designed, to mitigate, evade or diminish the impact of the identified risks, thereby closing the gap to avoid similar incidents from occurring in future. Operational risk incidents highlight that standardized and structural drivers within institutions allow these events to occur and hence this empirical study elucidates that the development and implementation of an ORM framework to curtail financial impact and protect the bank’s reputation is crucial and essential.